Страница 1 из 1

Что не так делаю?

Добавлено: Вт дек 22, 2009 4:52 pm
rax4
y''+5y'-6y=exp(t), нач условия y(0)=-1, y'(0)=0
Решение:
y=Y(p); y'=pY(p)+1;y''p^2)*Y(p)+p;exp(t)=1/(p-1).
(p^2)Y(p)+p+5(pY(p)+1)-6Y(p)=1(p-1)
Преобразуем:
Y(p)(p^2+5p-6)+(5+p)=1/(p-1);
Y(p)(p-1)(p+6)+(5+p)=1/(p-1);
Y(p)(p-1)(p+6)=[1/(p-1)]-(5+p);
Y(p)(p-1)(p+6)=[1-(5+p)(p-1)]/(p-1);
Y(p)=[1-(5+p)(p-1)]/[(p-1)(p-1)(p+6)];
Y(p)=1/[(p-1)(p-1)(p+6)] - (p+6-1)/[(p-1)(p+6)]=1/[(p-1)(p-1)(p+6)] - 1(p-1)+1/[(p+6)(p-1);
Фиг знает где ошибка